2005
DOI: 10.1111/j.1365-2982.2005.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a probiotic combination VSL# 3 and placebo in irritable bowel syndrome with bloating

Abstract: VSL# 3 reduces flatulence scores and retards colonic transit without altering bowel function in patients with IBS and bloating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
324
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(340 citation statements)
references
References 51 publications
7
324
2
7
Order By: Relevance
“…Several trials have been excluded from this list because of failure to compare with placebo (49) , re-analysis of old data (50) , unclear end points (51) or the use of multiple interventions (52) . Many early studies were small singlecentre trials (53)(54)(55)(56)(57) , although more recently a number of much larger multi-centre trials have been undertaken, reflecting the growing interest in the area (58)(59)(60)(61) .…”
Section: Probiotics In Irritable Bowel Syndrome: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials have been excluded from this list because of failure to compare with placebo (49) , re-analysis of old data (50) , unclear end points (51) or the use of multiple interventions (52) . Many early studies were small singlecentre trials (53)(54)(55)(56)(57) , although more recently a number of much larger multi-centre trials have been undertaken, reflecting the growing interest in the area (58)(59)(60)(61) .…”
Section: Probiotics In Irritable Bowel Syndrome: Clinical Trialsmentioning
confidence: 99%
“…No significant reduction in GI transit was found for the study group, although there was a symptom score reduction in abdominal bloating. Thus, a second, larger, trial was designed using forty-eight patients with a reduction in abdominal bloating as the primary end point and colonic transit and other symptoms as secondary end points (54) . Although only a non-significant reduction in abdominal bloating scores was found in the study group v. placebo (31 .…”
Section: Vsl#3mentioning
confidence: 99%
“…The same preparation (VSL#3) was used in only 3 studies. 69,77,80 Up to 8 different bacterial strains are used in some preparations and the combinations are numerous, since in many cases subspecies of specific strains were used that are only available to (and eventually patented by) individual companies. Two studies were performed by the same research group with the same preparation.…”
Section: Bacterial Strain Combinationsmentioning
confidence: 99%
“…17 Kim et al in another study suggested that effect of fiber and probiotics was different among the given organisms and IBS subtypes. 18 The present study patients rated the efficacy of global symptom assessment as grade 4 or above, suggesting a significant improvement in overall relief ( Figure 6). …”
Section: -14mentioning
confidence: 99%